Professional image of nursing and midwifery in East Africa: an exploratory analysis - Eunice Wambui Ndirangu; Ahmed Mohammed Sarki; Columba Mbekenga; Grace Edwards (BMC, 2021)
Abstract Background Evidence suggests that there is a negative image of nursing and midwifery that does not promote these professions as attractive career options. Furthermore, there is a paucity of studies documenting how nursing and midwifery is perceived in East Africa and where such studies exist they are country-specific. The aim of this study was to explore views regarding the image of nursing and midwifery among nurses and midwives in three East African countries, Kenya, Tanzania and Uganda. Methods An exploratory descriptive cross-sectional study administered online using Survey Monkey Questionnaires assessed the views and perceptions of nurses and midwives regarding the image of nursing and midwifery professions. Descriptive statistics and Pearson's Chi square tests were used to analyse the data. The semi-structured questions were analysed using content analysis. Results A total of 551 participants took part in the study. The majority were females (61.8%), registered nurses/midwives (45.8%), and aged 30-39 years (34.2%). Most of the respondents were from Kenya (39.7%) and Uganda (32.9%). About two-thirds of the nurses and midwives in this study perceived nursing/midwifery as both trusted and respected professions and expressed having a level of control over how their image was portrayed. Conversely, the nurses and midwives were conscious that the public had mixed responses about the nursing/midwifery professions specifically, some members of the public described nurses/midwives as professionals, knowledgeable and caring, others perceived nurses/midwives to be rude, cruel, unkind, lazy, unkempt, and maids. Conclusion This study offers an interesting insight about the image of nursing/midwifery in East Africa. Findings from this study will inform policy makers and educators about key concepts that affect the image of nursing and midwifery in East Africa. The findings will be used to design marketing materials to help improve the image of nursing and midwifery in the region and other African countries.